2005
DOI: 10.1111/j.1528-1167.2005.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Idiopathic Generalized Epilepsies

Abstract: Summary: Idiopathic generalized epilepsies (IGEs) are a relatively new category of disorders defined by strict clinical and electroencephalogram (EEG) features proposed by the International League Against Epilepsy (ILAE) classification of epileptic syndromes. IGEs are usually easy to diagnose when clinical and EEG data are collected, but epilepsy is not synonymous with epileptic syndrome. So far, IGEs are studied in the large group of epilepsies of undetermined or unknown etiology although the genetic origin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
188
3
19

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(223 citation statements)
references
References 49 publications
13
188
3
19
Order By: Relevance
“…Generalized myoclonic epilepsy in RR dogs reveals important parallels to JME, which is one of the most common forms of epilepsy in humans (14,(20)(21)(22)(23). As in humans, jerks are bilateral, arrhythmic, at times asymmetric, and predominate upon the upper limbs and trunk (20,21), whereby additional nodding movements of the head were present in some RRs.…”
Section: Discussionmentioning
confidence: 99%
“…Generalized myoclonic epilepsy in RR dogs reveals important parallels to JME, which is one of the most common forms of epilepsy in humans (14,(20)(21)(22)(23). As in humans, jerks are bilateral, arrhythmic, at times asymmetric, and predominate upon the upper limbs and trunk (20,21), whereby additional nodding movements of the head were present in some RRs.…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic generalized epilepsies (IGEs) account for 15-20% of all epilepsies and affect approximately 0.2% of the general population (Jallon and Latour, 2005). IGEs encompass several syndromes that are characterized by age-related, recurrent, unprovoked generalized seizures in the absence of detectable brain lesions or metabolic abnormalities (International League Against Epilepsy, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Seizures are known to be triggered by conditions such as sleep deprivation, sudden awakening, fatigue, alcohol intake, flashing lights, menstruation and stres. [1][2][3][4] It has been also demonstrated that spesific or nonspecific complex cognitive activities such as calculations, constructive activities, drawing, playing strategic board games are able to precipitate seizures.…”
Section: Introductionmentioning
confidence: 99%